Perubahan Konstelasi Politik dan Perlindungan Perempuan dan Anak di Lombok Tengah - Syaefullah - (Fakultas Hukum Universitas Mataram, 2015)
Political changes which we do through elections so far, actually will have implications on the order of a better life than before, in laying a better life, including changes for women, because cases of violence against women has not been well received attention it the bureaucracy, political parties and the local legislative body. This study aimed to see whether changes in the political constellation to give effect to the protection of women. The method used in this research is descriptive qualitative and qualitative analysis, through questionnaires, interviews and documentation study. The data used in this research is primary data obtained from informants directly related to this research, namely, bureaucracy, political parties and members of the Legislature. While secondary data is data obtained through researching reports, documents, and regulations related to the research. The results of this study indicate that, change the political constellation does have a significant influence for the protection of women in Central Lombok. Among the bureaucracy, although it has grown but still normative. Among politicians, despite all the political Parthians had gender equality programs but mostly just stay in the program alone, and do not possess the political agenda setting especially clear action agenda. Likewise among the legislature, there is no willingness to follow up on the protection of women's issues. In order to increase the protection of women in the bureaucracy, political parties, and the legislature is reached then, the authors give advice which may be related to changes in the political constellation and the protection of these women are: a strong commitment within the bureaucracy, the implementation of programs that have outlined the party central leadership on gender equality , large enough courage of the aggota legislative concerns the interests of the people, and the flexibility and delegation of authority to the representatives in the legislature by the political parties.